2021
DOI: 10.1161/circulationaha.120.050371
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Effects of Sodium Reduction

Abstract: Background: The relationship between dietary sodium intake and blood pressure (BP) has been tested in clinical trials and nonexperimental human studies, indicating a direct association. The exact shape of the dose–response relationship has been difficult to assess in clinical trials because of the lack of random-effects dose–response statistical models that can include 2-arm comparisons. Methods: After performing a comprehensive literature search for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(36 citation statements)
references
References 133 publications
(56 reference statements)
0
32
0
4
Order By: Relevance
“…Thus, the indifferent BPlowering effect following salt restriction in normotensive individuals is potentially related to differential activation of neuro-hormonal factors compared to patients with hypertension [58]. However, in additional meta-analyses, the exclusion of short-duration trials was associated with a significant BP-lowering effect independently of hypertension status [53][54][55][56][57]60].…”
Section: To What Extent Should Sodium Intake Be Lowered?mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the indifferent BPlowering effect following salt restriction in normotensive individuals is potentially related to differential activation of neuro-hormonal factors compared to patients with hypertension [58]. However, in additional meta-analyses, the exclusion of short-duration trials was associated with a significant BP-lowering effect independently of hypertension status [53][54][55][56][57]60].…”
Section: To What Extent Should Sodium Intake Be Lowered?mentioning
confidence: 99%
“…The most recent update of meta-analytical approaches is presented in Table 1 (Ref. [52][53][54][55][56][57][58][59][60]).…”
Section: To What Extent Should Sodium Intake Be Lowered?mentioning
confidence: 99%
See 1 more Smart Citation
“…This could be mainly due to the fact that dietary sodium restriction has a significant BP-lowering effect. A very recent and huge meta-analysis of 85 trials, mainly carried out on hypertensive patients, with sodium intake ranging from 0.4 to 7.6 g/day and follow-up from 4 weeks to 36 months, showed an approximately linear relationship between sodium intake and increase in both systolic and diastolic BP across the entire range of dietary sodium exposure [5]. Another meta-analysis of 17 cohorts with 457 participants showed that salt restriction was associated with a significant reduction in augmentation index (9.3%) as well as central systolic BP and central pulse pressure [6].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, an increase in potassium intake has been linked to decreasing blood pressure levels and stroke incidence, with an indication of a possible U-shape relationship with minimum risk at 3.5 g/day (i.e., 90 mmol/day) of potassium excretion [ 10 , 11 ]. Conversely, a decrease in sodium intake showed an approximately linear association with blood pressure levels [ 12 ], cardiovascular diseases [ 13 ], and stroke [ 14 ], with beneficial effects of sodium reduction in both subjects with and without hypertension [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%